Formulasi Sediaan Masker Stick Clay Dengan Kombinasi Ekstrak Daun Kelor (Moringa Oleifera Lamk) Dan Daun Sagu (Metroxylon Sagu Rottb) Serta Aktivitas Antioksidan - Putri, Risky Juliansyah; Halid, Nur Hatidjah Awaliyah; Himaniarwati, Himaniarwati; Nasir, Nur Herlina; Pusmarani, Jastria; Jannah, Nisa Fil (BORNEO JOURNAL OF PHARMASCIENTECH, 2026)
Antioxidants are beneficial for skin health, and they help to neutralize free radicals. These antioxidants are present in various plants, including Moringa and sago leaves. To enable easier application, these antioxidant properties are incorporated into cosmetic products, such as stick clay masks. The purpose of this research is to assess the formula's stability and the antioxidant effectiveness of stick clay mask formulations that combine extracts from Moringa and sago leaves. The study utilized a laboratory experimental design, and the samples were collected from Wolulu Village, Watubangga District, Southeast Sulawesi.. Stick clay mask containing extracts of sago and moringa leaves at 0.5%, 1%, and 1.5% concentrations. The formulation underwent a stability test, and the IC50 value was used to determine the antioxidant activity test using DPPH methods. In addition to having antioxidant activity at F0 263.51 µg/mL in the weak category, Formula FI 73.80 µg/mL in the strong category, F II 54.74 µg/mL in the strong category, and F III 30.11 µg/mL in the very strong category, the results of the stability test of the Stick clay mask have satisfied the requirements, which include organoleptic test, homogeneity test, spreadability test, adhesion test, and drying time test.